Efficacy of dual intracerebroventricular and intravitreal CLN5 gene therapy in sheep prompts the first clinical trial to treat CLN5 Batten disease - Murray, Samantha J.; Wellby, Martin P.; Barrell, Graham K.; Russell, Katharina N.; Deane, Ashley R.; Wynyard, John R.; Gray, Steven J.; Palmer, David N.; Mitchell, Nadia L. (Frontiers in Pharmacology, 2023)
Mutations in the CLN5 gene cause the fatal, pediatric, neurodegenerative disease CLN5 neuronal ceroid lipofuscinosis. Affected children suffer progressive neuronal loss, visual failure and premature death. Presently there is no treatment. This study evaluated dual intracerebroventricular (ICV) and intravitreal (IVT) administration of a self-complementary adeno-associated viral vector encoding ovine CLN5 (scAAV9/oCLN5) into CLN5 affected sheep (CLN5 -/-) at various disease stages. CLN5 disease progression was slowed in pre-symptomatic sheep who received a moderate dose of scAAV9/oCLN5, whilst a higher ICV dose treatment in early and advanced symptomatic animals delayed or halted disease progression. Intracranial (brain) volume loss was attenuated in all treatment cohorts, and visual function was also sustained in both the early and advanced symptomatic treated sheep over the 24month duration of the study. Robust CLN5 protein expression was detected throughout the brain and spinal cord, and improvements in central nervous system and retinal disease correlates were observed. These findings hold translational promise for extending and improving the quality of life in both presymptomatic and symptomatic CLN5 patients, and prompted the initiation of the first in-human Phase I/II clinical trial testing ICV/IVT administration of scAAV9 encoding human CLN5 (https://clinicaltrials.gov/; NCT05228145). disease state and allow evaluation of the long-term safety of the therapy and provide useful translational data regarding effective dose.